Effect of culture filtrate of three fungi in different combinations on the development of Dacus cucurbita in vitro - S.K. SAXENA, PURNIMA SINHA and (Indian Phytopathology, 2002)
Rhizoctonia solani, Trichoderma viride and Gliocladium virens were isolated from Cucurbitaceae fruits and tested for their antagonistic properties against D. cucurbitae [Bactrocera cucurbitae]. All of the fungi were antagonistic but G. virens was the most effective.